SIMULATION OF SEA WATER INTRUSION IN THE PLAIN OF ARGOS WITH ADVECTION - DISPERSION MODEL - Γιαννουλόπουλος Π. (Bulletin of the Geological Society of Greece, 2004)
The plain of Argos, southern Greece, is perhaps the first region in Greece where sea water intrusion in groundwater was noticeably observed since late fifties. Observed chloride concentrations, are mostly less than 1500 mg/l, in the affected zone, exhibiting smooth variations. Also, relevant water quality data, show that sharp fronts are not occurring. Thus, the transport of chlorides is assumed to be governed by advection and dispersion mechanisms rather than density dependent transport. In this paper the application of a distributed numerical model, based on advective and dispersive - chloride transport is described. Hence, the mathematical model of a "homogeneous fluid" and the "tracer" approach has been assumed rather that the "general" approach of the "heterogeneous fluid". This code has successfully replicated the measured concentrations of the calibration period (1964-69) and also the pertinent concentrations of the validation period (1969-750). In predictive simulation, a scenario of chloride flushing by natural recharge, without any pumping, was tested and it was calculated that rehabilitation period could be at least as long as twenty years. The weakness of this model involves both errors of conceptual model and numerical errors. The major conceptual problem is the lack of knowledge of pumping distribution, which constitutes the driving force of salinization, while numerical errors are mainly attributed to mass balance errors introduced in the Eulerian - Lagrangian implementation of the numerical model.